Seismic Performance of Earthquake-Resilient RC Frames Made with HSTC Beams and Friction Damper Devices. Issue 15 (18th November 2022) - Colajanni, Piero; La Mendola, Lidia; Monaco, Alessia; Pagnotta, Salvatore
ABSTRACT: Seismic behavior of RC frames with hybrid steel-trussed concrete beams is affected by panel zone damage due to a large amount of longitudinal reinforcement. Here the seismic efficiency of innovative frames characterized by friction damper devices (FDDs) at beam-to-column connections is compared against traditional frame. Three configurations are investigated: FDDs alone; FDDs with column-to-foundation connections having preloaded threaded bars and disk springs; FDDs with self-centering friction devices. Non-linear analyses show that FDDs alone prevent plastic hinge formation at beam ends and beam–column joint damage. FDDs with self-centering friction devices effectively limit both peak and residual drifts, avoiding column base plasticization.